An etude for post-pandemic practice: The impact of the COVID-19 pandemic on practice methods and instrumental technique - Fallowfield, Ellen; Gomez, Patrick (Frontiers in Psychology, 2022)
This paper considers how the pandemic-related concert-free time affected musicians’ practice, specifically in relation to technique. A semi-structured interview was carried out on 22 musicians based in Switzerland (11 males, 11 females; 7 students, 15 non-students; 11 with school-aged children, 11 without school-aged children; 16 with teaching duties and 6 non-teachers). The amount of practice during the pandemic-related concert-free time was reported as different to usual by 91% and usual for only 9% of participants (p = 0.002). Forty-one percent of participants reported reduced, and 41% ‘fluctuating’ amounts of practice. The proportion of practice time spent on technique was reported by 55% of participants to have increased and by only 9% to have decreased (p = 0.019). Of those who reported an increase in technique practice, 75% agreed this had a positive impact on technique, and only 8% disagreed (p = 0.037). Moreover, 58% considered this work to have changed their current and future practice. Participants were statistically more likely to report ‘never’ watching online tutorials than ‘often’ (p = 0.014), but, of those that did watch such material, 75% agreed that it had a positive impact upon their practice. Most participants created digital content during this period; only 5% produced no such material. An increased use of digital tools was reported by 55% participants, 92% of whom described this as having a positive effect upon practice and only 8% were unsure (p = 0.022). However, in the unstructured discussion, the use of digital tools appears to be associated with mixed outcomes. Men reported significantly more frequent use of digital tools (91% vs. 45% describing this use as often, p = 0.038) and spent a larger proportion of time on technique relative to their pre-pandemic habits than women (p = 0.065); moreover, a trend indicated that more women than men created digital content in the form of tutorials (p = 0.095). The exceptional situation musicians experienced during the pandemic, which introduced new aspects to musical instrument practice, and accelerated changes already underway, could lead to future work that improves practice under ‘normal’ conditions, and exposes discrepancies between certain demographic groups.